Serum Sodium and Potassium Levels in Senile Cataract Patients and Age ? Matched Normal Individuals - Junaid Nabi, Asmat Ara Mufti, Rayees Ahmad Sofi, Waseem Raja (Pakistan Journal of Ophthalmology, 2015)
Purpose: The purpose of the study was to compare the mean sodium and potassium levels in patients with senile cataract and age-matched normal individuals in Kashmir. Material and Methods: The study was designed as cross sectional observational study. 200 senile cataract patients scheduled for cataract surgery in the Department of Ophthalmology and 200 individuals of the same age group without cataract were selected. Mean serum sodium and potassium levels in the senile cataract group were calculated and compared with the control group. Serum sodium and potassium levels were measured by flame photometry technique. Statistical software SPSS-16 was used and means were compared between two groups by t-test. Since the study was a non interventional one, clearance was given by the department and study abides by the guidelines laid in the declaration of Helsinksi. Results: Mean serum sodium level in senile cataract patients and normal individuals was 139.60 ± 5.23 mEq/L and 137.15 ± 2.93 mEq/L respectively and there was statistically significant difference (p < 0.0001). Mean serum potassium level in senile cataract patients and normal individuals was 4.35 ± 0.574 mEq/L and 4.31 ± 0.45 mEq/L, and the difference was not statistically significant (p = 0.60). Conclusion: Serum sodium level in senile cataract patient was higher as compared to the control group. This outcome might suggest that increased dietary intake of the sodium leads to higher levels of serum sodium which in turn influences the cataractogenesis in senile patients. Keywords: Cataract, risk factors, sodium, dietary.